Relational spirituality and depression among married couples in Antigua - Reynolds, Conroy Everton (Mental health, religion & culture, 2016)
The World Health Organization indicates depression is the leading cause of disability worldwide. At the same time researchers have found religion/spirituality is inversely associated with depression. However, the mechanisms by which spirituality/religion impacts mental health have not been clearly identified particularly in non-western populations. Relational spirituality is a concept that focuses attention on the ways people relate to the sacred. This study examines whether different ways of relating to the sacred are implicated in levels of depression and whether marital partners affect each other’s level of relational spirituality and depression. Ninety-one (n = 91) married heterosexual couples in the Caribbean Island of Antigua completed measures of relational spirituality and depression. Data were analysed using path analysis and through Actor Partner Interdependence Model methods. Results of the analysis showed wives’ and husbands’ depression scores covaried (COV = 6.59, Pearson r = .28, p < .05). Three dimensions of relational spirituality predicted wives increased depression low disappointment scores (β = −.24, unstandardised B = −3.23, se = 1.30), and higher instability scores (β = .49, unstandardised B = 5.46, se = .96). The husbands’ disappointment (β = .21, unstandardised B = 2.17, se = .95) and instability (β = .54, unstandardised B = 4.65, se = .72) were positively related to their depression scores. The results demonstrate relational spirituality is a useful framework for addressing depression in individuals as well as married couples.